2017
DOI: 10.1002/masy.201600037
|View full text |Cite
|
Sign up to set email alerts
|

Falling Weight Impact Properties of Palm Shell Reinforced Palm Oil‐Based Polyurethane Bio‐Composite Sandwich

Abstract: Summary The research focused on the usage of waste oil palm biomass such as empty fruit bunch fibre (EFB), dried palm shell (DPS) and palm kernel shell (PKS) to produce palm oil‐based polyurethane (POPU) composite foams, and applied them as sandwich cores. The sandwich cores were attached with jute/epoxy composite facesheets to fabricate high‐strength bio‐composite sandwiches. Sandwich cores composed of 32 wt% of POPU binder, 8 wt% of EFB and 60 wt% of palm shells. Three palm shell systems from different blend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…EFB was used along with palm shells as reinforcement to the PUF core by Cheng et al Single palm shells and hybrid palm shells—consisting of dried palm shell (DPS) and palm kernel shell (PKS)—were used in the study. The flexural performance and falling weight impact response of the sandwich specimens were investigated.…”
Section: Puf Core Sandwich Structuresmentioning
confidence: 99%
“…EFB was used along with palm shells as reinforcement to the PUF core by Cheng et al Single palm shells and hybrid palm shells—consisting of dried palm shell (DPS) and palm kernel shell (PKS)—were used in the study. The flexural performance and falling weight impact response of the sandwich specimens were investigated.…”
Section: Puf Core Sandwich Structuresmentioning
confidence: 99%
“…Cheng et al [123] experimentally evaluated the flexural and compressive behaviors of bio-degradable sandwich panels with face sheets made of woven jute/vinyl ester and core composed of PU, 20phr EFB, and various amounts of dried palm shell and palm kernel shell. In addition, Cheng et al [124] investigated the impact behavior of bio-degradable POPU foam sandwich panels with jute-reinforced epoxy face sheets. Niedermann et al [125] investigated the properties of a new glucose-based epoxy resin and reported their good application for use in foam-core sandwich composites with jute and carbon-reinforced face sheets, even at high temperature up to 160°C.…”
Section: Sandwich Structures Made Of Non-wood Cellulose Natural Fibersmentioning
confidence: 99%
“…[177][178][179][180] deal with the behaviors of kenaf-reinforced epoxy core sandwich panels in thermal stability, bending, compression, impact, and water absorption. Zainol Abidin et al [181] performed an experiment to analyze the ballistic impact response of sandwich structures with kenaf-reinforced PU Bending [123], [125], [126], [127], [128], [129], [132], [133], [135], [137], [138], [139], [142], [146], [147], [148], [149] [110] [ 150], [151], [154], [155], [156], [157], [159], [160] [161], [162], [163], [166] Compression [123], [128], [132], [134], [135], [141], [143], [148], [149] - [154], [157] [164], [165] Impact/ crashworthiness [124...…”
Section: Sandwich Structures Made Of Kenaf Fibersmentioning
confidence: 99%